2016
DOI: 10.1016/j.clml.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Vascular Events Among Elderly Patients With Chronic Myeloid Leukemia: A Retrospective Analysis of Linked SEER-Medicare Data

Abstract: Elderly patients with CML had greater mortality and greater rates of MI, stroke, PE, and PAD than did noncancer patients. The event rates were not elevated among the TKI-treated (primary imatinib) patients, suggesting that the VE risk in these patients with CML was driven primarily by the underlying factors associated with CML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Two studies have assessed the risk of MI and ischemic stroke in patients with CML compared with non‐cancer patients . A study from the United States, based on linked Surveillance, Epidemiology, and End Results (SEER) cancer registry and Medicare Claims data for 1466 CML patients, reported an HR of 2.46 ( P < .001) for myocardial infarction and 1.54 ( P < .001) for ischemic and hemorrhagic stroke . Similar to our data, a more recent Swedish cohort study of CML patients during 2002‐2012 and age‐matched and sex‐matched individuals from the general population found incidence rate ratios of 1.9 (95% CI: 1.3 to 2.7) for myocardial infarction and 0.9 (95% CI: 0.5 to 1.5) for ischemic stroke .…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Two studies have assessed the risk of MI and ischemic stroke in patients with CML compared with non‐cancer patients . A study from the United States, based on linked Surveillance, Epidemiology, and End Results (SEER) cancer registry and Medicare Claims data for 1466 CML patients, reported an HR of 2.46 ( P < .001) for myocardial infarction and 1.54 ( P < .001) for ischemic and hemorrhagic stroke . Similar to our data, a more recent Swedish cohort study of CML patients during 2002‐2012 and age‐matched and sex‐matched individuals from the general population found incidence rate ratios of 1.9 (95% CI: 1.3 to 2.7) for myocardial infarction and 0.9 (95% CI: 0.5 to 1.5) for ischemic stroke .…”
Section: Discussionsupporting
confidence: 81%
“…Earlier studies have suggested that hematological cancers are associated with increased risk of myocardial infarction, but the existing literature has been contradictory for ischemic stroke . A Swedish population‐based cohort study of 18 627 multiple myeloma patients diagnosed from 1958 to 2006 and 70 991 age‐matched and sex‐matched individuals from the general population computed the 10‐year HRs for coronary artery disease (stable and unstable angina pectoris and myocardial infarction) and cerebrovascular complications (ischemic stroke, hemorrhagic stroke, and transient ischemic attack) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations